2022
DOI: 10.3390/ma15051853
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of Titanium Dioxide Nanomaterials from Agricultural Soil Amended with Sewage Sludge Incineration Ash: Comparison of a Pilot Scale Simulation with Standard Laboratory Column Elution Experiments

Abstract: Nanoscale titanium dioxide (nTiO2 (Hombikat UV 100 WP)) was applied to sewage sludge that was incinerated in a large-scale waste treatment plant. The incineration ash produced was applied to soil as fertilizer at a realistic rate of 5% and investigated in pilot plant simulations regarding its leaching behavior for nTiO2. In parallel, the applied soil material was subject to standard column leaching (DIN 19528) in order to test the suitability of the standard to predict the leaching of nanoscale contaminants fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Leaching tests represent a common thread in the submissions to this Special Issue [ 3 , 4 , 5 , 6 , 13 , 14 , 15 , 16 ]. The underlying mass transfer principles of column leaching tests are discussed by Liu et al [ 14 ], and Sakanakura et al [ 15 ] showed that adsorption parameters can be determined in batch leaching tests with varying liquid–solid ratios.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Leaching tests represent a common thread in the submissions to this Special Issue [ 3 , 4 , 5 , 6 , 13 , 14 , 15 , 16 ]. The underlying mass transfer principles of column leaching tests are discussed by Liu et al [ 14 ], and Sakanakura et al [ 15 ] showed that adsorption parameters can be determined in batch leaching tests with varying liquid–solid ratios.…”
mentioning
confidence: 99%
“…However, sewage sludge contains pollutants which are transferred to the ash. Meisterjahn et al [ 16 ] investigated the leaching of engineered nanomaterials from SSA which could be a component of sewage sludge as a result of residues from consumer products in waste water.…”
mentioning
confidence: 99%